Effects of E2/P4 Oral Capsules on Bone Turnover in Women With Vasomotor Symptoms [06F]. (May 2020) - Kagan, Risa; McClung, Michael R.; Graham, Shelli; Bernick, Brian; Mirkin, Sebastian; Constantine, Ginger
Abstract : INTRODUCTION: Menopausal hormone therapy slows bone turnover and reduces the risk of osteoporotic fractures. The objective of this post hoc analysis was to evaluate bone turnover markers (BTM) in the phase 3 REPLENISH trial, which evaluated vasomotor symptoms (VMS) with an oral estradiol/progesterone (E2/P4) in postmenopausal women with a uterus. METHODS: Eligible women for this analysis had ≥50 moderate to severe VMS/week, <5 years since last menstrual period, and BTM measurements at baseline, and months 6 and 12. Percent changes for 3 BTM (bone specific alkaline phosphatase [BSAP], C-terminal telopeptide of type I collagen [CTX-1], and N-terminal propeptide of type I procollagen [PINP]) assessed by immunoassay methods were evaluated from baseline to months 6 and 12 for the 1/100, 0.5/100 and placebo groups. RESULTS: A total of 157 women (40-61 years, 69% white) were analyzed (56 for each 1/100 and 0.5/100; 45 for placebo). Mean baseline values ranged from 14.0-14.3 U/L for BSAP, 0.34-0.39 ng/mL for CTX-1, and 76.9-79.3 ng/mL for PINP. Mean differences in percent change from baseline versus placebo significantly decreased with both E2/P4 doses for all 3 BTM at months 6 and 12. Mean differences from placebo for E2/P4 at months 6/12 ranged from -8.1% to -17.8% for BSAP (all, P⩽0.02), -30% to -41% for CTX-1 (all, P⩽0.001), and -14% to -29% for PINP (all, P⩽0.007). CONCLUSION: REPLENISH data provide support for a potential skeletal benefit of E2/P4 when used for the treatment of moderate to severe VMS.